(untitled) (Eurasian Journal of History, Geography and Economics, 2024)
In this article, the processes of formation of Kashkadarya rural tourism and its role in the life of our country, the theoretical and practical bases of activity in this field, the areas with the possibility of implementing this activity together with the points of rural tourism are researched. Also, the article describes the prospects of rural tourism development in Kashkadarya region, providing employment to local residents through rural tourism, improving the infrastructure of the region, and attracting foreign and local tourists.